2022
DOI: 10.1172/jci148667
|View full text |Cite|
|
Sign up to set email alerts
|

Stromal oncostatin M cytokine promotes breast cancer progression by reprogramming the tumor microenvironment

Abstract: The tumour microenvironment (TME) is reprogrammed by cancer cells and participates in all stages of tumour progression. The contribution of stromal cells to the reprogramming of the TME is not well-understood. Here we provide solid evidence of the role of the cytokine Oncostatin M (OSM) as central node for multicellular interactions between immune and nonimmune stromal cells and the epithelial cancer cell compartment. Oncostatin M Receptor (OSMR) deletion in a multistage breast cancer model halted tumour progr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 80 publications
(124 reference statements)
2
36
0
Order By: Relevance
“…As the IL6-JAK-STAT3 signaling pathway was upregulated both in the 4T1-Sca-1 + population and Tu-Gr1 + CD11b + -primed 4T1 cells (Figure 3A, B), we next examined the expression of Osm , Osmr , Il6st , Il6 , and Il6 receptor ( Il6ra ) in the Sebastian dataset (Figure 3G). The expression of Il6 and Osm was restricted to myeloid cells, with Osm expression being more prominent, similar to a previous report (33). Osmr was predominantly expressed in tumor cells, while Il6st and Il6ra were homogenously expressed in all cell types.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As the IL6-JAK-STAT3 signaling pathway was upregulated both in the 4T1-Sca-1 + population and Tu-Gr1 + CD11b + -primed 4T1 cells (Figure 3A, B), we next examined the expression of Osm , Osmr , Il6st , Il6 , and Il6 receptor ( Il6ra ) in the Sebastian dataset (Figure 3G). The expression of Il6 and Osm was restricted to myeloid cells, with Osm expression being more prominent, similar to a previous report (33). Osmr was predominantly expressed in tumor cells, while Il6st and Il6ra were homogenously expressed in all cell types.…”
Section: Resultssupporting
confidence: 91%
“…Besides directly activating tumor cells, OSM has also been shown to remodel macrophages and fibroblasts of the TME (33, 36). Araujo et al recently reported that OSM derived from tumor-infiltrating myeloid cells reprogram fibroblasts to secrete VEGF and the chemokines CXCL1 and CXCL16, resulting in enhanced myeloid cell recruitment and breast cancer progression (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some cases, OSM can promote tumor progression. Overexpression of OSM and OSMR has been detected in various cancers, including gastric, colorectal, breast, and glioma [ 38 , 39 ]. OSM-OSMR signal transduction plays a vital role in inflammation, oxidative stress, hematopoiesis, and development and is increasingly considered an essential factor in tumor progression [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In breast carcinoma, hypoxic epithelial tumor cells overexpress and release high levels of OSM, favoring the recruitment and M2 polarization of macrophages [ 54 ]. Moreover, myeloid-cell-derived OSM can drive CAFs to a pro-carcinogenic phenotype, showing increased contractility and secretion of soluble mediators, leading to immune cells’ accumulation and further supporting breast cancer development [ 55 ].…”
Section: Biological Activity Of Oncostatin Mmentioning
confidence: 99%